2018
DOI: 10.1101/453480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared heritability and functional enrichment across six solid cancers

Abstract: Quantifying the genetic correlation between cancers can provide important insights into the mechanisms driving cancer etiology. Using genome-wide association study summary statistics across six cancer types based on a total of 296,215 cases and 301,319 controls of European ancestry, we estimate the pair-wise genetic correlations between breast, colorectal, head/neck, lung, ovary and prostate cancer, and between cancers and 38 other diseases. We observed statistically significant genetic correlations between lu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 65 publications
7
47
2
2
Order By: Relevance
“…[4][5][6] For example, our estimate for testicular cancer closely matches the previous family-based estimate of heritability (h 2 =0.25; 95% CI: 0.15-0.37), 3 as well as a previous estimate of array-based heritability (h 2 =0.30; 95% CI: 0.08-0.51). 4 For lung cancer, our estimated heritability of h 2 =0.15 (95% CI: 0.10-0.20) approaches the twin-based estimate of h 2 =0.18 (95% CI: 0.00-0.42), 2 exceeds the array-based estimate from a study using the same methodology (h 2 =0.08; 95% CI: 0.05-0.10), 6 and is comparable to an earlier array-based estimate using individual-level data (h 2 =0.21; 95% CI: 0.14-0.27). 4 For rectal (h 2 =0.11; 95% CI: 0.07-0.16) and bladder (h 2 =0.08; 95% CI: 0.04-0.12) cancers, our heritability estimates are close to those from twin/family studies -h 2 =0.14 (95%CI: 0.00-0.50) 2 and h 2 =0.07 (95% CI: 0.02-0.11), 3 respectively.…”
Section: Genome-wide Heritability and Genetic Correlationsupporting
confidence: 83%
See 3 more Smart Citations
“…[4][5][6] For example, our estimate for testicular cancer closely matches the previous family-based estimate of heritability (h 2 =0.25; 95% CI: 0.15-0.37), 3 as well as a previous estimate of array-based heritability (h 2 =0.30; 95% CI: 0.08-0.51). 4 For lung cancer, our estimated heritability of h 2 =0.15 (95% CI: 0.10-0.20) approaches the twin-based estimate of h 2 =0.18 (95% CI: 0.00-0.42), 2 exceeds the array-based estimate from a study using the same methodology (h 2 =0.08; 95% CI: 0.05-0.10), 6 and is comparable to an earlier array-based estimate using individual-level data (h 2 =0.21; 95% CI: 0.14-0.27). 4 For rectal (h 2 =0.11; 95% CI: 0.07-0.16) and bladder (h 2 =0.08; 95% CI: 0.04-0.12) cancers, our heritability estimates are close to those from twin/family studies -h 2 =0.14 (95%CI: 0.00-0.50) 2 and h 2 =0.07 (95% CI: 0.02-0.11), 3 respectively.…”
Section: Genome-wide Heritability and Genetic Correlationsupporting
confidence: 83%
“…1 Efforts toward cancer prevention, screening, and treatment are thus imperative, but they require a more comprehensive understanding of the underpinnings of carcinogenesis than we currently possess. While studies of twins, 2 families, 3 and unrelated populations [4][5][6] have demonstrated substantial heritability and familial clustering for many cancers, the extent to which genetic variation is unique versus shared across different types of cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant genetic correlations with FEV1 and FVC were observed for lung cancer overall, in smokers, and for tumors with squamous cell histology, but not adenocarcinoma. Jiang et al 25 reported a similar magnitude of genetic correlation with FEV1/FVC, but did not observe an association with FVC, and did not assess FEV1. Differences in our results may be attributable to their use of GWAS summary statistics for pulmonary phenotypes from the interim UK Biobank release.…”
Section: Discussionmentioning
confidence: 95%